Interview with Ines Pasic (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
The interview with Ines Pasic, a Bosnian-born artist based in Peru, delves into her journey in the world of animation theater and music. Initially a pianist, Pasic discovered a new form of expression in pantomime and object manipulation, often combining these arts with music in her performances. She discusses the influence of her travels and experiences in different cultures on her musical and theatrical creations. Her shows frequently explore personal themes and are marked by physical expressiveness and the integration of music as a narrative and atmospheric element.
Keywords: Ines Pasic; Body puppets; Puppetry; Puppet theater; Migration.